2019
DOI: 10.1155/2019/6046037
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Direct Shear Test on Scrap Tire Strip Reinforced Brick Powder

Abstract: In order to clear the shear mechanism of the scrap tire strips reinforced brick powder, a series of large-scale direct shear tests were carried out on the pure brick powder and reinforced brick powder. The scrap tire strips with 50 mm in length, 5 mm in thickness, and 10 mm, 30 mm, and 50 mm in width were put into the brick powder with volume percentages of 2%, 6%, and 10% as reinforcement, respectively. The results show that the internal friction angle and cohesion increase by adding scrap tire strips into br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…e stiffness of the concrete particles is far greater than that of the tire patch, and the tire patch will penetrate into the tire patch after bearing the force. A similar mechanism of action between brick powder particles and tire slices was confirmed by Ma et al [15]. At this time, the tire will give a reaction force to the concrete particles and increase the cohesion and friction in the sample.…”
Section: 5supporting
confidence: 73%
See 1 more Smart Citation
“…e stiffness of the concrete particles is far greater than that of the tire patch, and the tire patch will penetrate into the tire patch after bearing the force. A similar mechanism of action between brick powder particles and tire slices was confirmed by Ma et al [15]. At this time, the tire will give a reaction force to the concrete particles and increase the cohesion and friction in the sample.…”
Section: 5supporting
confidence: 73%
“…Ghazavi and Sakhi [12] mixed tire slices of different sizes and contents into sandy soil and investigated the shear strength and the deformation properties of the mixed soil through large-scale direct shear tests. Similar direct shear tests obtained the same conclusion that the tire reinforced composite soil could improve its shear strength and reduce the deformation [13][14][15]. After a lot of tests, it is found that the mechanical properties of the tire were not the same when it is mixed with different materials.…”
Section: Introductionmentioning
confidence: 58%
“…It was concluded that the use of high-impact polystyrene and foam glass can be considered as a useful way of utilization waste. Further analysis of the use of plastics by [11,12] and [13,14] proved the effective use of tire scraps in the stabilization process. The addition of different proportions of the tire scraps improved the strength properties of the soil at an optimum quantity of the tire scraps.…”
Section: Introductionmentioning
confidence: 99%
“…Researching on the mechanical properties of soil cured by solid waste, Akbulut et al [27] conducted unconfined compression, shear box, and resonant frequency tests on clayey soils modificated by scrap tire rubber and synthetic fibers to investigate their strength and dynamic properties. Ma et al [28] studied the shear strength characteristics and working mechanism of the scrap tire strips treated brick, in terms of large-scale direct shear test. According to research by Vieira and Pereira [29], construction waste mixtures are mainly composed of bricks and concrete, and the mechanical properties of construction waste show low variability.…”
Section: Introductionmentioning
confidence: 99%